WOMEN SCIENTISTS IN KAZSSR DURING THE LATE SOVIET ERA - Kubeyeva, Lunara (Nazarbayev University School of Sciences and Humanities, 2024)
With the creation of the Soviet Union, the Bolsheviks introduced policies aimed at equalizing and emancipating women in Central Asia. The emancipation campaign involved education and the rejection of the traditional way of life for Central Asian women to turn them into a labour force, a source of childbearing, and to construct socialism. Since the 1930s women started working in a variety of professions, including science, education, agriculture, and medicine. However, women scientists had to go through a lot of challenges during this process. I argue that there was a gender inequality within Soviet Academia. Female scientists were in an unequal position with male colleagues owing to the public discourse about main gender roles. The argument will be based on the study of archival documents, newspapers and magazines, films, as well as interviews. My respondents were women scientists who started or developed their scientific careers at universities and departments of the Academy of Sciences of the Kazakh SSR during 1960 -1980s. The purpose of my study is to explore both the professional experiences and daily routines and practices of women scientists, the ways through which they developed their careers and how they performed their gender roles as wives and mothers. My study will contribute to the fields of gender studies and history of Soviet Kazakhstan and Soviet Central Asia. The work will show the nature of Soviet policy towards women in Central Asia on the example of the Academy of Kazakhstan and analyse the impact of this policy on their daily lives.
Keywords: Type of access: Restricted; Academy of sciences; gender studies